The archaeology of contemporary America - Caraher, William R. 1972- (University Press of Florida, 2024)
"This book provides a survey of contemporary archaeology in the United States, demonstrating the plurality of theoretical and methodological approaches that make this discipline in the U.S. unique
Includes bibliographical references and index
Keywords: Social archaeology / United States; Material culture / United States; Urban archaeology / United States; Household archaeology / United States; Excavations (Archaeology) / United States; Archéologie sociale / États-Unis; Culture matérielle / États-Unis; Archéologie urbaine / États-Unis; Fouilles (Archéologie) / États-Unis; SOCIAL SCIENCE / Archaeology; SOCIAL SCIENCE / Anthropology / Cultural & Social; Excavations (Archaeology); Household archaeology; Material culture; Social archaeology; Urban archaeology; United States